COMMUNICATION STRATEGY OF AS-SUNNAH ISLAMIC BOARDING SCHOOL IN RESTORING ITS IMAGE AFTER IDENTITY CONFLICT IN BAGIK NYAKE - rahmatullah, siti; Fahrurrozi; Malik, Abdul (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The objectives of this research were, (1) to be able to explain the situation of the As-Sunnah Islamic boarding school after the identity conflict in Bagik Nyake. (2) To be able to analyze the communication strategies of the As-Sunnah Islamic boarding school after identity conflict in Bagik Nyake. This research used qualitative approach with type of case study. Data collection was carried out by using observation, interview and documentation techniques. The intensive research process was carried out almost a year involving various informants consisting of Islamic boarding school leaders, teachers, students of the As-Sunnah Islamic boarding school in Bagik Nyake and the community. The results of this research showed that the situation of the As-Sunnah Islamic boarding school after identity conflict with the community was as usual the students directly continued their school and various Islamic boarding school activities also continued. The communication strategies carried out by the As-Sunnah Islamic boarding school in restoring its image after identity conflicts were by (1) the relationship function, namely discussing with the community by attending each other's activities but still without leaving the sunnah of Rasulullah PBUH. (2) The education function, namely combining the general curriculum and the Islamic boarding school curriculum. (3) the persuasion function, namely conducting studies every Tuesday night, Tabligh Akbar activities with interviewee from the Middle East and publishing various Islamic boarding school activities on social media such as Facebook, so that this could improve or increase the good image of the As-Sunnah Islamic boarding school. (4) problem solving, namely by convincing the students’ parents and the community that Islamic boarding school is the right Islamic boarding school for their children in terms of religious learning in accordance with what was taught by Rasulullah PBUH. Keywords: Communication Strategies, Image, Identity Conflict.